Sustainable Latent Fingermark Detection Protocols for Remote-Location and Resource-Limited Jurisdictions - Bouzin, Jemmy Terence (Curtin University, 2023)
This thesis proposes the concept of frugal forensics, establishing the first systematic framework for sustainable forensic science service provision, with an emphasis on latent fingermark detection in resource-limited jurisdictions. The application of frugal forensics was successfully demonstrated through the development of sustainable latent fingermark detection techniques for Seychelles. The adoption of such methods in support of the UN SDGs is key in bridging the gap in forensic science services that exist in the Global South.